2019
DOI: 10.1073/pnas.1901442116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polypeptides via bioinspired polymerization of in situ purified N -carboxyanhydrides

Abstract: All polymerizations were conducted in a water/DCM biphasic system in the presence of PEG−PBLG macroinitiators. [I] 0 = 0.5 mM except for the last three entries. ELG, γ-ethyl-L -glutamate; ZLL, e-carboxybenzyl-L -lysine. † Polymerization time reaching 98% monomer conversion. ‡ Obtained MW (designed MW*). § Synthesis of block copolymer through sequential monomer addition. [I] 0 = 1.0, 0.5, and 0.25 mM for the first, second, and third block, respectively. Song et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(165 citation statements)
references
References 43 publications
9
156
0
Order By: Relevance
“…After the 2-h polymerization in DCM, the end-group analysis showed <1% loss of terminal amine groups 19 , indicating negligible chain termination 10,12 . In addition, owing to the fast polymerization kinetics and the water-immiscibility of DCM 20,21 , the polymerization of NCA in DCM in the presence of 10 vol% water still resulted in well-defined polypeptide with predictable MW, similar to that obtained under anhydrous conditions (Fig. 2d and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 57%
“…After the 2-h polymerization in DCM, the end-group analysis showed <1% loss of terminal amine groups 19 , indicating negligible chain termination 10,12 . In addition, owing to the fast polymerization kinetics and the water-immiscibility of DCM 20,21 , the polymerization of NCA in DCM in the presence of 10 vol% water still resulted in well-defined polypeptide with predictable MW, similar to that obtained under anhydrous conditions (Fig. 2d and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 57%
“…Finally, Cheng et al. reported the in situ purification of NCA during ROP when the polymerization was conducted in a CH 2 Cl 2 /water emulsion …”
Section: Methodsmentioning
confidence: 99%
“…[12] Finally,C heng et al reported the in situ purification of NCA during ROP when the polymerization was conducted in aC H 2 Cl 2 /water emulsion. [13] Unfortunately,t he preparation of nanoassemblies from amphiphilic polypeptides requires as econd step of nanoprecipitation (Scheme 1A), which entails the addition of an onsolvent for the hydrophobic segment to ac opolymer solution in ac ommon solvent for both blocks. [14] This nanoprecipitation step is typically performed from toxic organic solvents,under relatively diluted conditions (< 1wt%)and is sensitive to scale,o verall hampering eventual regulatory approval.…”
mentioning
confidence: 99%